2005
DOI: 10.1152/ajpheart.00165.2004
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α induces proliferation or apoptosis in human saphenous vein smooth muscle cells depending on phenotype

Abstract: . TNF-␣ induces proliferation or apoptosis in human saphenous vein smooth muscle cells depending on phenotype. Am J Physiol Heart Circ Physiol 288: H293-H301, 2005. First published September 9, 2004; doi:10.1152/ajpheart.00165.2004.-Tumor necrosis factor (TNF)-␣ is implicated in development of restenotic and atherosclerotic vascular lesions, which are pathological processes involving both proliferation and apoptosis of vascular smooth muscle cells (VSMCs). Human VSMCs were recently found to contain heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
(125 reference statements)
2
34
0
2
Order By: Relevance
“…Recently, TNF-α was shown to have a different effect on spindle-shaped versus epithelioid SMCs isolated from the human saphenous vein. 41 Whereas spindle-shaped SMCs showed increased proliferation after TNF-α treatment, epithelioid SMCs were induced to undergo apoptosis. Similarly, angiotensin II has been shown to induce apoptosis in epithelioid but not in spindle-shaped SMCs isolated from the rat aorta.…”
Section: Biochemical Factorsmentioning
confidence: 99%
“…Recently, TNF-α was shown to have a different effect on spindle-shaped versus epithelioid SMCs isolated from the human saphenous vein. 41 Whereas spindle-shaped SMCs showed increased proliferation after TNF-α treatment, epithelioid SMCs were induced to undergo apoptosis. Similarly, angiotensin II has been shown to induce apoptosis in epithelioid but not in spindle-shaped SMCs isolated from the rat aorta.…”
Section: Biochemical Factorsmentioning
confidence: 99%
“…First of all, a-actin immunostaining was employed to distinguish SMCs from the other cell types in the tunica media of the SV segments [12]. a-SM actin was previously detected in all stages of SMCs development [8]. We found that ageing of CABG patients had weak impact of a-SM actin immunostaining in the studied SMCs.…”
Section: Discussionmentioning
confidence: 75%
“…They also produce tissue inhibitors of metalloproteinases (TIMPs), and a balance between MMPs and TIMPs eventually determines the local homeostasis of the ECM [7]. Moreover, the population of venous SMCs was reported to be heterogeneous regarding metabolic, proliferative and chemotactic activities [8]. Subtypes of SMCs were characterized by altered expression of smooth muscle proteins such as a-smooth muscle actin (a-SM actin), smooth muscle myosin heavy chain (SM-MHC), calponin (CALP) and cytokeratin [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations